PENDAMPINGAN KADER KESEHATAN DAN ORANG TUA ANAK BERKEBUTUHAN KHUSUS TENTANG MENGGOSOK GIGI DI METESEH - Sukini Sukini; Irmanita Wiradona; Prasko Prasko (Poltekkes Kemenkes Semarang, 2024)
Children with special needs have a higher susceptibility to oral health problems. Factors that contribute to this include difficulty in cleaning teeth, limited motor coordination, and certain medical conditions. So that a comprehensive approach is needed that involves cadres and parents in assisting maintaining dental health in children with special needs. This community service implements a method of empowering health cadres and parents in an effort to assist brushing teeth in children with special needs. The assistance begins with the formation and training of health cadres. Health cadres are then involved in assisting parents of children with special needs regarding proper brushing techniques and habits. Furthermore, parents assist in the process of brushing the teeth of children with special needs for 21 days. The implementation of this program aims to improve the skills and habits of brushing teeth in children with special needs. The program of assisting parents and health cadres in brushing teeth in children with special needs through the empowerment method has proven effective in improving tooth brushing behavior in children with special needs.